Pengembangan Pariwisata (Community Basic Tourism) Dalam Meningkatkan Pendapatan Masyarakat Di Desa Bissoloro Perspektif Ekonomi Islam - bahrun, sriwahyuni; Fathurrahman; Muhammad Nasri Katman (AT TAWAZUN: Jurnal Ekonomi Islam, 2024)
This research aims to determine the role of the community in tourism development, tourism development from an Islamic Economics perspective and the impact of tourism development in increasing community income in Bissoloro Village. This research is qualitative research that creates descriptions in the form of words. Data collection was carried out using interview techniques and secondary data. Furthermore, to analyze the data, this research was carried out using data validity tests using trust, transferability, dependency and certainty tests. The research results show that the role of the community in tourism development in Bissoloro Village has been involved, some of the people in Bissoloro Village play a role as managers, providing services and as ordinary people who help managers with cleanliness and security. Then, in developing tourism from an Islamic Economic perspective, tourism development in Bissoloro Village includes attractions, facilities, accessibility and training that have been well developed and in accordance with Islamic Economics where the community has preserved nature well, the management has provided friendly facilities for Muslim visitors. and managers receive training in tourism development. Furthermore, the impact of tourism development in increasing people's income in Bissoloro Village is the opening of new job opportunities for the community and increasing people's income.